Recommendations for a National FDI Strategy and Roadmap for Uzbekistan : New Sources of Growth - World Bank (Washington, DC, 2022)
The development of a new foreign direct investment (FDI) strategy for Uzbekistan comes at an important moment to support Uzbekistan’s new development objectives. The report provides core inputs and elements for the government of Uzbekistan to develop a new FDI strategy and roadmap to unlock new sources of growth. It leverages an assessment of Uzbekistan’s historical FDI performance and policy context and provides an analysis of current megatrends affecting the global landscape for FDI to identify sectors with high growth potential for FDI attraction in Uzbekistan. It articulates a vision and specific objectives related to FDI attraction for Uzbekistan and presents explicit, quantifiable objectives and targets to help maximize the contribution of FDI to Uzbekistan’s overall economic development goals. It considers relevant historical FDI trends as well as regional and global FDI trends and provides in-depth analysis of the feasibility and desirability of key sectors for FDI attraction that were selected with guidance from the government. To support effective implementation, the presented strategy should be underpinned by a detailed reform action plan and roadmap and a comprehensive monitoring and evaluation framework that can be applied by the government to monitor progress with implementing the FDI strategy.